The Role of Islamic Boarding Schools in Human Resource Development - Nanang Rusliana; Ari Arisman; Fuad Hilmi (Journal of Society and Development, 2022)
Islamic boarding schools are one of the non-formal educational institutions that make a major contribution to the Indonesian nation, currently Islamic boarding schools not only provide religious knowledge whose status is only non-formal education will open up formal education in efforts to develop human resources This research aims to discuss the role of Islamic boarding schools in development human resources at Syarif Hidayatulloh Islamic Boarding School (Syahida). This research uses descriptive qualitative method. Research subjects were selected by purposive sampling. Data collection techniques include: observation, interviews, and documentation. The research subjects were the Pondok Leaders, community leaders, and students. Data analysis techniques use data collection, data reduction, data display, and verifying. The results and discussion of this study indicate that the Syarif Hidayatulloh Islamic Boarding School has a role in human resource development. This is evidenced by data verification with a data assessment rubric, that the results of observations, interviews, and documentation show that there has been an increase in human resources thanks to the role of the Syarif Hidayatullah Islamic Boarding School. This research concludes that Islamic boarding schools have a role in human resource development.